Pelatihan model pembelajaran daring untuk meningkatkan kompetensi guru di Kabupaten Bekasi - Paristiowati, Maria; Yusmaniar, Yusmaniar; Karepesina, Mohammad Asrul Ashmi; Umayah, Anisa (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
There has been a COVID-19 pandemic outbreak since the end of 2019 requiring learning not to be carried out in school but as distance learning (PJJ). Technology plays an important role in PJJ such as learning through video, learning video, learning web applications, or video conference using any platforms. Teachers as facilitators must have skills in technology and creating fun learning models that can facilitate the student in PJJ. So, it is necessary to carry out the activity to update the knowledge and skills of teachers so that they can adapt to pandemic conditions by conducting a fun online learning models training for teachers. Therefore, they can create an interesting online learning that can motivate and facilitate PJJ according to the 2013 Curriculum. As an area that is very close to Jakarta, Bekasi Regency is located just to the east of Jakarta, so it is appropriate that Universitas Negeri Jakarta as a higher education institution makes Bekasi Regency the target area for the training. This training was conducted on 18th of September, 202l, located at SMP Negeri 2 Tarumajaya with 25 participants consist of teachers from several schools in Bekasi Regency. This training used a combination of methods like presentation, discussions, demonstration, and Q&A session. The result of this training shows that participants can add new insight regarding the application of fun online learning models for students during the pandemic and have responded positively to the training that is organized by Department of Chemistry Education UNJ